Efficacy and tolerability of Arnophyte cream for herpes infection, in subjects with early signs and symptoms of recurrent HSV-2 - Salkar, Kavita S.; Chotalia, Chetna S.; Salvi, Rajiv Y.; Mehta, Nimesh D.; Tripathi, Anirudh T. (International Journal of Research in Dermatology, 2019)
Background: Arnophyte® cream developed from Ficus arnottiana plant extract showed strong potential as an Anti-viral agent. The objective of the study was to evaluate the efficacy and tolerability of Arnophyte® cream in subjects with early signs and symptoms of recurrent HSV-2. Methods: The treatment was given for a period of 14 days. The study outcomes measured were assessment of reduction in pain using the visual analogue score (VAS), the changes in the quality of life index for recurrent genital herpes (GHQoLr); physician’s and patient’s global assessment of the therapy, signs and symptoms associated with HSV-2 and healing of the target lesion on baseline, day 2, day 4, day 7 and day 15. Results: Arnophyte® cream showed significant reduction in the signs and symptoms of herpes infection. The cream was well tolerated with no serious adverse events observed. Conclusions: Arnophyte® cream can be considered as a possible therapeutic option for the treatment of recurrent herpes infections in both HSV-1 and HSV-2.